Decoupling growth from degradation: a CS-ARDL and MMQR panel analysis of ecological footprints and sustainable economic growth - Shi, Shilin; Smith, Lisa (Frontiers in Environmental Science, 2025)
This study examines how natural resource rents, technological advancement, renewable energy use, and economic growth affect ecological footprints in ten developing economies (Brazil, China, Bangladesh, South Africa, India, Pakistan, Indonesia, Mexico, Russia, and Ethiopia) from 1990 to 2020. Using advanced econometric techniques, including CS-ARDL and MMQR models, the analysis tests both long-run and distributional relationships while addressing cross-sectional dependence and heterogeneity. The results indicate that renewable energy use and technological innovation significantly reduce ecological footprints, supporting the Environmental Kuznets Curve hypothesis in these contexts. Additionally, environmental taxes and regulations are found to mitigate environmental degradation effectively. However, continued reliance on fossil fuels remains a major challenge for these economies. The study’s findings highlight the need for stronger environmental governance, investment in green technologies, and policy reforms to promote sustainable development. By providing robust empirical evidence, this research contributes to the literature on sustainable growth strategies in resource-dependent developing countries.